Thailand: Case Studies of Filial Piety, Family Dynamics, and Family Finances - Unexpected Findings of a Country-Wide Research of The Evaluation of Project Performance Supported by Older Persons Fund - Sringernyuang, Luechai (Animo Repository, 2020)
Asian values, the aging population, and financial assistance programs for the elderly form the backdrop for this manuscript. The rationale of this manuscript is to analyze the unexpected findings from the research project “The Evaluation of Project Performance Supported by Older Persons Fund,” which indicated a connection between filial piety, family dynamics, and how family finances were spent and managed. The objective is to study this phenomenon in more detail to elucidate changes in family structures that are traditionally held as the lynchpin of Asian society. The manuscript applied two separate methodologies: Part A is a mixed methods methodology that is required for the objectives of “The Evaluation of Project Performance Supported by Older Persons Fund.” Part B employed the qualitative approach of case studies analysis and coding by Glaser and Strauss (2017). A total of 22 case studies were analyzed using this method for connections between filial piety, family dynamics, and family finances. The outcome of the coding analysis of the case studies was then subjected to further analysis using the concepts of phenomenology (internalization, externalization, intersubjectivity) as per the works of Berger and Luckmann (1991). The results suggest changing patterns of filial piety, namely, new dimensions of filial piety, lateral and diagonal family dynamics, and negative filial piety. From the standpoint of phenomenology, new identity formations, as well as the transition from one identity to another, are experienced by the elderly; internalization of changes that surround them financially leads to externalization of identities that are still capable and economically viable; flexibility of roles played within the family are subject to negotiations and intersubjectivity. Demographic changes bring added challenges to the management of the elderly, their finances, and their roles within the traditional family structure of filial piety.